Numerical Analysis of Six Degrees of Freedom Motion Response of Trimaran Semi-Submersible Ship - Musdika Bagas Satria Putrananda; Aldias Bahatmaka; Widya Aryadi; Berliana Ayarent Puteri; Christian Imanuel Hutagalung (Mekanika)
This study examines the motion response characteristics of a trimaran semi-submersible vessel, with a focus on its performance in tourism applications where passenger comfort is a primary concern. Using ANSYS AQWA simulation software, this analysis integrates diffraction and radiation theory with potential flow theory to evaluate the six degrees of freedom (surge, sway, heave, roll, pitch, and yaw) under various wave conditions, including different frequencies and directions based on the Joint North Sea Wave Project (JONSWAP) spectrum. Simulations were performed on waves with heading angles ranging from 0° to 180°. The simulation results were validated based on previous studies both experimentally and numerically. The results show that the sway peaks at 8 m/m for heading angles of 90°, while the surge reaches a maximum of 8 m/m at 0° and 180°. The heave motion resonates between 2.2 rad/s with a peak amplitude of 3 m/m at 90°. Pitch motion at heading angles of 0° reaches 40 °/m at 3.5-4 rad/s. Roll motion remained within acceptable limits (9 °/m), and yaw peaked at 13 °/m at 45° and 135°. These findings suggest that, although the trimaran exhibits stable performance in most motion responses, design improvements are necessary to mitigate excessive pitch motion and enhance passenger comfort in tourism applications.